The poor’s opportunities of participation in economy digitalization - A. V. Pavlov (Вестник университета)
The subject of this study is to identify social problems among the poor in the process of digitalization of the economy and to develop proposals for their elimination. The scientific novelty lies in the presentation of the position that in order to involve the poor population in the digitalization of the economy, who need state social assistance, it is not enough to provide its traditional types – due to the lack of legally prescribed duties and (or) economic incentives necessary to perform certain actions. One of these types of state social assistance to the poor is its socio-economic stimulation – combining both state social assistance and economic incentives. An approximate sequence of measures for the socio-economic simulation of the poor population regarding its involvement in the processes of digitalization is presented. The methodological basis of the research consists of general scientific methods – analogies, analysis, synthesis, formal-logical, as well as special methods – comparative and descriptive analysis, and other methods. The relevance of the topic is due to the lack of norms in legislation regulating public relations regarding the participation of the poor in digitalization.